Brown Plant Insect (Nilaparvata lugens) Pathogen On Rice (Oryza Sativa) - Zulyusri, Zulyusri; Anugrah, Chici (International Journal Labs, 2023)
Brown stem planthopper (Nilaparvata lugens Stal.) is the primary rice pest. This study aims to determine the Pathogen of the Brown Planthopper Insect (Nilaparvata lugens) on Rice Plants (Oryza Sativa) with the literature review method using Google Scholar and Taylor French journals that have ISSN from sinta 1-6. Many farmers have experienced a decrease in the productivity of rice farming caused by pests, one of which is the brown planthopper. The brown planthopper is a pathogen for rice plants that destroys the plants by sucking the liquid from the stems until the rice plants become dry. One of the characteristics of rice plants attacked by brown planthopper pests is that they turn yellowish.